Targeting regulatory T cells for cardiovascular diseases - Wang, Xinting; Zhou, Hua; Liu, Qian; Cheng, Peipei; Zhao, Tingyao; Yang, Tianshu; Zhao, Yue; Sha, Wanjing; Zhao, Yanyan; Qu, Huiyan (Frontiers in Immunology, 2023)
Cardiovascular diseases (CVDs) are the leading cause of death and disability worldwide. The CVDs are accompanied by inflammatory progression, resulting in innate and adaptive immune responses. Regulatory T cells (Tregs) have an immunosuppressive function and are one of the subsets of CD4+T cells that play a crucial role in inflammatory diseases. Whether using Tregs as a biomarker for CVDs or targeting Tregs to exert cardioprotective functions by regulating immune balance, suppressing inflammation, suppressing cardiac and vascular remodeling, mediating immune tolerance, and promoting cardiac regeneration in the treatment of CVDs has become an emerging research focus. However, Tregs have plasticity, and this plasticity Tregs lose immunosuppressive function and produce toxic effects on target organs in some diseases. This review aims to provide an overview of Tregs' role and related mechanisms in CVDs, and reports on the research of plasticity Tregs in CVDs, to lay a foundation for further studies targeting Tregs in the prevention and treatment of CVDs.